Evaluation of the effect of spinosad on lipid peroxidation and antioxidant markers in female mice - Saadi, Leila1; Bouazza, Marwa; Mokrane, Ahlam; Aicha, Meriem; Lebaili, Nemcha (University of Eloued جامعة الوادي, 2018)
A Like any synthetic substance, or even natural, pesticides can produce harmful effects on human and animal health. The purpose of the present study is to evaluate the oxidative profile following the exposure of female mice to 9.2 mg/kg/day of spinosad. This is to examine the relationship between insecticide exposure and the risk of developing oxidative stress. Adult mice of the Naval Medical Research Institute were given by gavage daily for 18 days with spinosad, at rate of 9.2 mg/kg/day. Short-term exposure caused lipid auto-oxidation, expressed as an increase in malondialdehyde concentration in treated mice. Lipid peroxidation is associated with high level of plasma total anti-oxidative power and low level of plasma vitamin C. These results support the toxicity of the bioinsecticide witch induce oxidative stress in female mice
Articale in International Journal of biological and Agricultural Research Vol. 01 N. 02
Keywords: Bioinsecticide, Spinosad, Toxicity, Oxidative stress, Female mice